Dialogical Approach to Improving Arabic Pronunciation - Maghfurin, Ahmad; Mufiduddin, Gus Asyabab (Nurul Jadid University, 2023)
Pronunciation plays an important role in the process of learning foreign language because it leads learners to a better understanding of speech and improves their ability to communicate. Many students have difficulties in learning Arabic because it differs from their mother tongue and have made mistakes in different attributes, one of which is the pronunciation of their letters. This research aims to show common errors in the pronunciation of Arabic words, the reasons for those mistakes and how to fix them through dialogue at the Pondok Pesantren Tarim al-Ghonna-Samarang. This research is qualitative descriptive without statistical methods of detecting facts through data collection and description of their nature in order to find specific causes. This research is based on the method of direct observation, and then the interview with teachers and students of the Institute on its Arabic language education activities, in addition to the analysis of the relevant documents. At the end of the research, we concluded that word pronunciation errors are common among the students in daily dialogues, leading to a change of meaning and misunderstanding between the speakers and the listeners. The reasons for these mistakes are that they are not used to uttering some Arabic letters that do not exist in their native language, in addition to their lack of Arabic vocabularies. The conversation activities are very effective in correcting the pronunciation of Arabic words, as we were able to detect the mistakes directly made by the students and then to treat them at each mistake or postponed at the end of the dialogue activity.